Dampak Ekonomi dan Pembangunan Infrastruktur Pascapemekaran Wilayah Kecamatan Rowokangkung Tahun 1992-2020 - Arsalam, Dawud (Department of History, Faculty of Humanities, Diponegoro University, 2024)
The formation of Rowokangkung District in Lumajang Regency in 1992 was a product of Indonesia's decentralization policy. This study examines the district's economic and infrastructural development following its establishment to assess the policy's effectiveness. Employing a historical research methodology, the study reveals that while the district has experienced some infrastructural improvements, such as irrigation, roads, and electricity, economic growth has remained predominantly agrarian-based. A key finding is the top-down nature of the district's formation, with limited community involvement in the decision-making process. This lack of participatory governance contributed to a mismatch between policy planning and local needs, ultimately hindering economic development.The territorial splits policy tends to be top-down without involving substantial community and local government participation. This indicates a gap between planning policies and real needs at the local level. Limited economic impact: Although the wheels of government are running well, the expansion has not been able to drive significant economic growth in Rowokangkung District